2020
DOI: 10.31577/geogrcas.2020.72.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Kde sa chodí voliť? Faktory ovplyvňujúce geografické rozloženie volebnej účasti v slovenských parlamentných voľbách

Abstract: Where do voters appear at ballots? Factors influencing the geographical distribution of voter turnout in Slovak parliamentary electionsElectoral results are significantly influenced by voter turnout, and the explanation of differences in turnout has received considerable academic attention. However, a systematic investigation of the geography of voter turnout in Slovakia has not been conducted yet. The objective of the study is, first, to present a map of voter turnout in parliamentary elections in Slovakia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Last but not least, turnout was shown to be high in municipalities with a higher proportion of Slovaks, which is entirely in line with mobilisation theory. However, it is questionable how much of an impact this has on low voter turnout in municipalities with a higher representation of the Hungarian and Roma minorities, as previous research has shown (Kevický, 2020b;Kevický & Daněk, 2020). Thus, the higher turnout in municipalities with a higher representation of Slovaks may reflect less interest in elections among national minorities.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Last but not least, turnout was shown to be high in municipalities with a higher proportion of Slovaks, which is entirely in line with mobilisation theory. However, it is questionable how much of an impact this has on low voter turnout in municipalities with a higher representation of the Hungarian and Roma minorities, as previous research has shown (Kevický, 2020b;Kevický & Daněk, 2020). Thus, the higher turnout in municipalities with a higher representation of Slovaks may reflect less interest in elections among national minorities.…”
Section: Discussionmentioning
confidence: 95%
“…Exploring mutual relationships of attributes in aggregate units by utilising the OLS analysis proved to be vital in a large number of studies analysing voter turnout (e.g. Kostadinova, 2003;Kerwin Kofi & Stephens Jr., 2013;Kevický & Daněk, 2020). However, the OLS analysis, like other global regression models, can provide only for results that represent average coefficient values for the whole unit of analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only five geographical studies dealt exclusively with the issue of turnout, and all of them have come out in the last 10 years (Mikuš and Gurňák 2014;Kevický 2020a;Kevický and Daněk 2020). These studies seek to map the uneven distribution of turnout, some of which also try to identify several factors influencing voter turnout "maps" in Czechia and Slovakia (Kevický 2020b;Kevický and Daněk 2020).…”
Section: Topics Of Studymentioning
confidence: 99%
“…Of the studies focused on the issue of turnout, only three make use of theory, for instance, societal modernization theory, mobilization theory, or habitual voting theory (Kevický 2020a;Kevický and Daněk 2020). The remaining studies work with grievance theory (Maškarinec and Bláha 2014), the conceptual sociological structure of city (Kerekeš 2020), and the theory of phantom borders (Šimon 2015).…”
Section: Theoretical Background Of Studymentioning
confidence: 99%